Blood pressure variability in subacute stage and risk of major vascular events in ischemic stroke survivors. Issue 10 (October 2019) - Kang, Jihoon; Kim, Beom Joon; Yang, Mi Hwa; Jang, Myung Suk; Han, Moon-Ku; Lee, Ji Sung; Gorelick, Philip B.; Lee, Juneyoung; Bae, Hee-Joon
Abstract : Background: We aimed to investigate whether blood pressure (BP) in the subacute stage of ischemic stroke affects subsequent vascular events after acute ischemic stroke. Methods: From a prospective stroke registry database, consecutive ischemic stroke patients arriving within 48 h of onset were identified. The mean and SD of SBP per patient (SBPmean and SBPSD ) in the subacute stage (from 72 h of onset to discharge), were calculated. Primary outcome was a composite of stroke, myocardial infarction and vascular death that occurred within 1 year after hospital discharge. A Cox proportional hazards model was applied to elucidate whether the increase of SBPmean and SBPSD would increase the hazards of the primary outcome. Results: Of 4415 patients (age, 66.7 ± 13.2 years; men, 69.5%), mean ± SD of SBPmean and SBPSD in the subacute stage was 137.3 ± 15.4 and 13.3 ± 3.9 mmHg, respectively. Primary outcome events occurred in 6.9% during the first year after stroke. There was a significant dose–response relationship between the SBPSD and the risk of the primary outcome ( P  = 0.004), but not between SBPmean and the risk ( P  = 0.78). Interpolating the change of adjusted hazard ratio using restricted cubic spine function suggested an existence of a threshold effect of SBPSD and a U-shaped relationship of SBPmean for the composite event. Conclusion: This study shows that BP variability but not mean BP in the subacute stage of ischemic stroke may increase 1-year risk of major vascular events in patients surviving its acute stage. Abstract : Supplemental Digital Content is available in the text